High-pressure phase behavior of polycaprolactone, carbon dioxide, and dichloromethane ternary mixture systems - Gwon, J.; Shin, H.Y.; Kim, S.H.; Kim, H. (Korean Institute of Chemical Engineers, 2015)
The high-pressure phase behavior of a polycaprolactone (Mw=56,145 g/mol, polydispersity 1.2), dichloromethane, and carbon dioxide ternary system was measured using a variable-volume view cell. The experimental temperatures and pressures ranged from 313.15 K to 353.15 K and up to 300 bar as functions of the CO2/dichloromethane mass ratio and temperature, at poly(D-lactic acid) weight fractions of 1.0, 2.0, and 3.0%. The correlation results were obtained from the hybrid equation of state (Peng-Robinson equation of state + SAFT equation of state) for the CO2-polymer system using the van der Waals one-fluid mixing rule. The three binary interaction parameters were optimized by the simplex method algorithm. ？ 2015, Korean Institute of Chemical Engineers. All rights reserved.